Pathomechanisms in demyelination and astrocytopathy: autoantibodies to AQP4, MOG, GFAP, GRP78 and beyond. Issue 3 (June 2022) - Mader, Simone; Kümpfel, Tania; Meinl, Edgar
Abstract : Purpose of review: The purpose of this review is to highlight the recently emerging pathomechanisms of diseases associated with autoantibodies to AQP4, MOG, GFAP, GRP78 and further novel targets. We discuss novel biomarkers and therapeutic approaches. Recent findings: Although complement-mediated cytotoxicity (CDC) is regarded as the major effector mechanism for AQP4-IgG in neuromyelitis optica spectrum disorders (NMOSD), recent studies helped to understand the relevance of complement-independent effector mechanisms. For MOG-IgG mediated diseases the role of CDC is less clear. MOG-IgG may trigger a tightly controlled FcR and BTK-driven microglia proliferative response in MOG-antibody-associated diseases. Differences of antibody-mediated tissue damage may reflect differential response to therapy. In addition, antibodies to GFAP, GRP78 and further novel targets have been implicated in demyelination and astrocytopathy. Summary: Elucidating the whole spectrum of effector functions in diseases mediated by AQP4-IgG and MOG-IgG and understanding the role of additional novel autoantibodies involved in demyelination and astrocytopathy may guide further novel treatment decisions.